An Overview of Thermal Plasma Arc Systems for Treatment of Various Wastes in Recovery of Metals - Samal, Sneha; Blanco, Ignazio (Materials (Basel, Switzerland), 2022)
Thermal plasma systems are being used for the recovery of metals from complex waste and minerals. The latter contain multiphase metals in various forms that are extremely tedious to separate. Thermal plasma arc melts the waste and minerals for qualitative plasma products for powder industries. In this overview, we briefly report a description of the various thermal plasma systems and their uses in recovering metal from metal-containing materials in the form of waste or minerals. Various plasma arc systems, such as transferred, nontransferred, and extended arc, have enabled the development of an efficient and environmentally friendly way to recover valuable metals from industrial wastes such as red mud and minerals such as ilmenite.
Keywords: minerals; thermal plasma; waste; metal; recycling